Social Studies Learning Problematics in MtsN 1 Pariaman City - Mulyana, Fitri; Ananda, Azwar; Fatimah, Siti (International Journal of Educational Dynamics, 2023)
Social studies is one of the subjects that is taught in an integrated manner at the Junior High School (JHS) level. This integrated learning raises problems in social studies learning. The purpose of this study is to identify problems in social studies learning. The method used is the qualitative method. The informants used were teachers and students from seven JHS/MTsN. Data collection methods were interviews, observation, and documentation. Data analysis using descriptive analysis. Based on the results of the study, two problems can be identified, namely 1) Lack of Learning Facilities and Infrastructure, where in social studies learning in class VII MTsN 1 Pariaman City there is a lack of existing learning support facilities. This makes it an obstacle when the teacher explains material that requires learning support media such as pictures and videos. The lack of media in the classroom, such as Liquid Crystal Display (LCD) Projectors that are often used are only teaching materials or books and student worksheets, so learning is not interesting; and 2) Less Varied Learning Methods, where the method most often used by social studies teachers in MTsN 1 Pariaman City in social studies learning is the lecture method. due to a lack of books. If you use other methods such as discussion, students must have books to read so that there is material for discussion.